Determination of Tetracycline in Water and Honey by Iron(II, III)/Aptamer-Based Magnetic Solid-Phase Extraction with High-Performance Liquid Chromatography Analysis. (3rd July 2019) - Tu, Chunyan; Dai, Yuanyuan; Xu, Ke; Qi, Mengyu; Wang, Weiping; Wu, Liang; Wang, Aijun
Abstract: A novel aptamer-based adsorbent was prepared for the magnetic solid-phase extraction of tetracycline. The Fe3 O4 /aptamer adsorbent was fabricated by immobilizing an aptamer on the surface of Fe3 O4 magnetic nanoparticles by the reaction between avidin and biotin. The parameters affecting the isolation efficiency such as the pH, extraction time, extraction temperature, eluent, and elution time were investigated in detail. Under the optimal conditions, a linear relationship between the peak area and the concentration of tetracycline was observed in the range from 10.0 to 3000.0 µg L −1 with a correlation coefficient of 0.9985 and a limit of detection of 2.5 µg L −1 . The developed method was successfully employed for the determination of tetracycline in honey and water samples with recovery values from 82.9 to 107.3% and relative standard deviations less than 7.6%. Compared with previously reported methods for the determination of tetracycline, the proposed protocol provides improvements in the limit of detection and specificity with reduced consumption of adsorbent and organic solvents.